Role of the avian retroviral protease in the activation of reverse transcriptase during virion assembly. - Craven, R C (1991)
The retroviruses of the avian sarcoma-leukosis virus group synthesize their viral protease (PR) in two precursor forms--as a carboxy-terminal domain of the Gag precursor and as an embedded domain within the Gag-Pol precursor. We have shown previously that the Gag-derived PR is fully capable of processing the Gag precursor in the absence of the embedded PR (R.P. Bennett, S. Rhee, R.C. Craven, E. Hunter, and J.W. Wills, J. Virol. 65:272-280, 1991). In this study, we examined the question of whether or not the PR domain of Gag-Pol has an essential role in the maturation of the Pol proteins. The Gag-Pol precursor was expressed in the absence of Gag by use of a simian virus 40-based vector in which the gag and pol reading frames were fused. The fusion protein accumulated to high levels in transfected cells without being released into the medium but could be rescued into particles by coexpression of the Gag protein from a second vector. The resulting particles contained mature Gag and Pol proteins and active reverse transcriptase (RT). Using this complementation system, the effects of PR defects in the Gag and/or Gag-Pol proteins on the activation of RT were examined. The results showed that the presence of a functional PR on the Gag precursor, but not on Gag-Pol, was required for full activation of RT. The embedded PR of Gag-Pol was unable to carry out any detectable processing of the Gag precursor and was able to activate RT to only a low level in the absence of a functional Gag PR domain. Finally, some point mutations in the Gag-Pol PR domain inhibited activation of RT in trans by a wild-type PR, suggesting that the correct conformation of the PR domain in Gag-Pol is prerequisite for activation of RT.